VACCINATION AGAINST THE FLU AMONG CHILDREN WITH DISTURBANCES IN STATES OF HEALTH AND CHRONIC DISEASES - L.S. Namazova; V.K. Tatochenko; S.G. Aleksina; M.G. Galitskaya; Z.A. Izvol'skaya; A.G. Il'in; V.N. Sadovnikova; O.V. Chumakova (Педиатрическая фармакология)
The present textbook for the doctors highlights the latest data on the flu spread, its clinical manifestations, as well as opportunities for its prevention and treatment. The authors especially carefully described the methods of immunoprophylaxis, including specific like type. They listed all the registered vaccines and vaccines of local and foreign origin to be registered in the Russian federation, methods of their injection, probable undesirable phenomena. Specific stress was laid onto the own personal data of the authors as to application of the vaccines against the flu among both healthy children and those, who suffer from various disturbances or chronic diseases, including pernicious run. The textbook was approved at the meeting of the scientific council of the general directorate, scientific center of children's health, Russian academy of medical sciences, on September 14, 2006.